Editorial Note: Changes in Makara Human Behavior Studies in Asia - Jaya, Edo S (Makara Human Behavior Studies in Asia, 2021)
The year 2021 is a time of change. The COVID-19 pandemic is still raging in most parts of the world. The 4.0 industry revolution is still going faster than ever. As changes occur everywhere we are also forced to adapt and change here in Makara Human Behavior Studies in Asia. Since the beginning of this year, we have been migrating to a new website based on Digital Commons from BE Press. The process is not yet completed as there are many editions to be migrated and information to be filled in the new website. I am grateful for the support of our publisher, Directorate of Administration, Data, and Management of Research Product and Innovation (DADPPRI UI), for providing this facility. Special thanks are warranted to Hanun Thalia who has provided extra effort to help us migrate and make sure that this edition publishes on time. We are grateful to Early Melati, Nathalia Bella Christiana, and Kai Riantoputra who have aided during this critical period of our journal. But most of all I am grateful to our managing editor Dr. Muhammad Abdan Shadiqi who plays a significant role in pushing through the painful changes that we must make in these turbulent times. I am most thankful to him for this new layout of the journal. I find the design to be modern and more readable. I hope that the readers find that too. On top of that, we are broadening our types of submission. We recognize the importance of review articles in helping policymakers during this pandemic era, and we want our journal to facilitate too. We will now accept review articles in the form of meta-analysis, systematic reviews, and scoping reviews.